1980
DOI: 10.1212/wnl.30.9.981
|View full text |Cite
|
Sign up to set email alerts
|

Herpetic brainstem encephalitis

Abstract: A fatal case of brainstem encephalitis presented as an acute lateral medullary syndrome. Pathologic examination showed a focal encephalitis along the roots and the intramedullary portion of the right vagus and glossopharyngeal nerves. Herpesvirus particles were demonstrated by electronmicroscopy of formol-fixed material. This is the second known case of herpetic brainstem encephalitis confirmed by postmortem examination and the only one in which the infection was limited to the brainstem. This case and a revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

1982
1982
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(12 citation statements)
references
References 0 publications
1
10
0
1
Order By: Relevance
“…In patients, recurrent brain stem encephalitis has been reported, but the case number is much less than for encephalitis localized in the frontal and/or temporal cortex (20,36,37). Our present study employed mice inoculated with virus by the ocular route, which mimics natural infection in some humans and has been the most frequently used model for investigating HSV reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…In patients, recurrent brain stem encephalitis has been reported, but the case number is much less than for encephalitis localized in the frontal and/or temporal cortex (20,36,37). Our present study employed mice inoculated with virus by the ocular route, which mimics natural infection in some humans and has been the most frequently used model for investigating HSV reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…However, in these reports pathological changes indicating HSE were not limited to the brain stem, but were found also in the temporal lobe, frontal cortex, cingulate gyrus, occipital lobe or cerebellum [8,9]. The circumscribed nature of HSV infection limited to the brain stem has been histologically documented in only two cases [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Their MRI showed that the responsible sites are comparable with those reported in experimental studies 1-3. Herpes simplex virus type 1 (HSV-1) infection also causes brainstem lesions7 8 characterised by acute onset of multiple cranial nerve palsies, ataxia, and pyramidal tract involvement. Disturbances of consciousness and respiration are not uncommon.…”
mentioning
confidence: 99%